Bersama Lawan Demam Berdarah Dengue: Edukasi dan Aksi Pencegahan DBD di Kabupaten Aceh Besar - Farrah Fahdhienie; Tiara Mairani; Irma Hamisah; Fahrisal Akbar (Jurnal Surya Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) is a public health problem that remains a threat, especially in tropical regions like Indonesia. Miruek Lamreudeup Village is an area at high risk of dengue fever transmission due to the environment that supports the breeding of the Aedes aegypti mosquito. This community service activity aims to increase public knowledge and awareness through education and concrete actions to prevent dengue fever. The implementation method includes counseling, distribution of abate powder, and distribution of dengue prevention pocket books to 45 participants consisting of heads of families, housewives, and youth. Evaluation was carried out with a pre-test and post-test using a multiple-choice questionnaire. The pre-test results showed that all participants (100%) were in the low knowledge category. After the education, there was a significant increase, with 80% of participants reaching the high knowledge category and 20% the moderate category. In addition to increasing knowledge, this activity also stimulated active community participation in discussions and direct implementation of mosquito larvae control in their respective homes. This activity has proven effective in increasing public awareness and understanding of dengue fever prevention. The suggested follow-up plan includes the formation of jumantik cadres, post-activity monitoring, and collaboration with village governments and health centers to create sustainable prevention efforts.